Application of technology of problem-based learning in the discipline «Methodology of carrying out school chemical experiment» - Abeuova, S.B.; Naushabekova, D.D.; Muslimova, D.M.; Abeuova, E.B.; Tussupbekova, E.K.; Dyussekeyeva, A.T. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article presents the results of an experiment on the application of problem-based learning technology in teaching chemistry. Problem learning is aimed at the independent search for new knowledge and ways of action, and also involves a consistent and purposeful promotion of cognitive problems, through the resolution of which students actively learn new knowledge. Technology of problem-based learning was used in the discipline «Methodology of carrying out of school chemical experiment» with the students of the third course. Two demonstration experiences in chemistry were chosen as problem situations in our case. Updating of knowledge was carried out before the experiment. Then there was the creation of a problem situation and the formulation of the problem. The chemical experiment was shown by a teacher. The situations were considered by students. Then conclusions were drawn. The questionnaire of A.A. Rean and V.A. Yakunin was used for diagnostics of educational motivation of students. Knowledge of problem situations was tested with the test method before and after the experiment. To identify opinions of students on the technology of problembased learning the individual interviews were conducted. As a result of application of technology of problembased learning cognitive and research interest, search features and abilities were created, opportunities for cooperation of the teacher with students were opened that promoted deeper and strong assimilation of material. Despite the disadvantages of problem learning, including high time costs, the presence of the necessary «starting» level of knowledge of students, today the idea of problem learning has been successfully implemented in the systems of developmental education.
Проблемалық оқыту технологиясын «Мектепте химиялық экспериментті жүргізу əдістемесі» пəні сабақтарында қолдану
Применение технологии проблемного обучения на занятиях по дисциплине «Методика проведения школьного химического эксперимента»
Keywords: problem-based learning; problem situations; new technologies of teaching chemistry; chemical experiment; methods of teaching chemistry